Technology Acceptance Model Dalam Penerapan Sistem Pajak Online Di Kota Madiun - N Nuryanto (INVENTORY: JURNAL AKUNTANSI, 2021)
The purpose of this study was to determine the factors that influence the acceptance of information technology systems by teachers in the Madiun City Government by using the Technology Acceptance Model. This research model adopted directly from the research of Tangke (2004) by using perceptions of usefulness and ease of use, which are independent variables and actual use as dependent variables. Data in the form of a questionnaire were collected using the online survey method. The number of questionnaires was 400 questionnaires distributed, 64 of which were successfully collected and can be analyzed. The method of analysis using multiple regression methods. The results of this study indicate that the perceived usefulness and convenience of users have a significant effect on the real use variable.Keywords: Information technology systems; perceived usefulness; ease of user; and actual